Pajak Reklame: Efektivitas, Laju Pertumbuhan dan Kontribusi Pada Pendapatan Asli Daerah - Widiyani, Zenny; Rakhmawati, Ita (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Cenderawasih, 2025)
This study aims to determine the effectiveness, growth rate, and contribution of billboard tax to local revenue in Pati Regency in 2021-2023. Using a descriptive quantitative approach, the object of research is billboard tax in Pati Regency, with the subject of research conducted through the Regional Financial and Asset Management Agency (BPKAD). Secondary data sources came from the BPKAD Revenue Division, and data collection was carried out through observation, interviews, and documentation. The population of this research is billboard tax. Supporting data is obtained from various literatures such as books, journals, and previous research. The analysis technique used includes the calculation of effectiveness, growth rate, and contribution of billboard tax with a special formula, processed to produce clear and objective information. The results showed that the effectiveness of billboard tax was rated “Very Effective” with an average of 119.09%, the growth rate of billboard tax was “Less Successful” with an average of 6.15%, and the contribution of billboard tax was “Very Insufficient” with an average of 0.34%. Keywords: effectiveness; growth rate; contribution; billboard tax; local revenue